HEAVY METALS ACCUMULATI ON IN SOIL, WATER, MAIZE AND CHICKEN AT ORI-ILE BATTERY WASTE DUMPSITE, OLODO, IBADAN, NIGERIA (2016)
Battery waste consists of toxic Heavy Metals (HMs) and the Ori-Ile battery waste dumpsite, Olodo, Ibadan has elicited public health concerns. Available literature revealed that maize absorbs and accumulates toxic HMs from polluted soils of irrigated farmlands. But, there is limited information on its accumulation in chicks fed with maize-based feeds at Olodo, where maize is predominantly grown for poultry feed and human consumption. This study was designed to investigate accumulation of some HMs in soil, water, maize and chicks from the vicinity of Ori-Ile battery waste dumpsite, Olodo, Ibadan, Nigeria. An auto-battery Waste Dumpsite (WD), Ori-Ile, Olodo was purposively selected for the study. One hundred and samples l six topsoithirty were purposively collected (every two months, 2009) July to2008March from waste dumpsite and along North, South, East and West (N,S,E,W) directions at 5 m intervals from the edge of WD. Thirty two groundwater samples were collected 25 m away from . directionsW E,S,N, along WD Control soil and water samples were collected from Moor Plantation (MP), Ibadan. Soil and groundwater samples were analysed for HMs. Maize was planted in Direction with Highest HMs Concentration (DHHMC) for three months. The maize-parts weregrains) leaves, stems, (roots, harvested and analysed for HMs. Broiler feed protein) crude 19.7%-(18.8 was formulated from part of harvested-grains using standard method. Thirty broilers (day-old) were obtained from a farm, acclimatised for two-weeks on commercial feed and subdivided into two equal groups. The broilers were then fed on Formulated Feed from Harvested Grains (FFHG) and Formulated Feed from Control Grains (FFCG) for additional six weeks. Five chicks from each broiler group were sacrificed at four, six and eight-week old to determine lead, cadmium and iron accumulation in plasma, skin, liver and femur. Similar organs from Free-Range Chicks around WD (FRCMP) MP and (FRCWD) were also analysed for metals. Histopathological analysis of chicks’ liver and kidney were done using standard procedure. The HMs in all samples were determined using atomic absorption spectrophotometry. Contamination, Bio-concentration and Bio-accumulation Factors BaF) and BcF (CF, were determined for soil, maize and chicks respectively using standard methods. Data were analysed using descriptive statistics, ANOVA and T-test at p=0.05. iii The HMs concentration (mg/kg) from the WD was 123.1,±258.4 :Cd 1436.7,±4273.8:Pb 791.5±7910.0:Fe while that for 94.8,±274.3 :Cd 1107.9,±4693.8 :Pb :North 740.0;±8346.7 :Fe South: 867.0,±4353.3:Pb 603.5;±8189.6:Fe 71.4,±255.2:Cd 65.6,±248.2:Cd 832.9,±4351.3 :Pb :East 639.5; ±8130.0:Fe West: 1020.8,±4698.3 , 676.8±7851.3 86.9,±278.4 respectively. These were significantly higher than control 353.9)±976.3 1.2,±2.2 39.8,±(157.0 and NESREA limits 50).:Cd 164,:(Pb Soil CF values were greater than 6 indicating severe contamination. The HMs concentrations in groundwater 0.002, ±0.003:Cd 0.015,±0.017:(Pb mg/L) 0.015±0.033:Fe were significantly higher than control but less than NESREA limits 1.0). :Fe 0.005,:Cd 0.01,:(Pb Lead and cadmium in DHHMC maize-parts were significantly higher than control. Roots had concentration of . mg/L 0.19±2.84:Cd and 1.98±40.95:Pb In all maize-parts, BcF of HMS was < 1. Four-week old FFHG broilers’ liver had highest lead, cadmium and iron 0.003,±0.011 0.002,±(0.014 ly) respective mg/L 28.023±302.01 where four- weeks>six-weeks>eight-weeks. In FFHG and FRCWD chicks, lead and cadmium were significantly higher than FFCG and FRCMP. Lead and cadmium BaF values for all chicks were < 1 while iron was > 1. In FRCWD, lead iron and 0.015)±(0.068 8.48)±(298.0 were highest in the liver, while 0.002) ±(0.013 cadmium was highest in the skin. Necrosis, severe diffused hepatic degeneration and interstitial haemorrhages were observed in FFHG and FRCWD chicks. High accumulation of heavy metals found in the soils of Ori-Ile battery waste dumpsite, Olodo, Ibadan bio-accumulated in maize-roots and in chicken organs.